Principal evaluation in the United States: A national review of state statutes and regulations - Nielsen, Sarah R.; Lavigne, Alyson L. (Education Policy Analysis Archives, 2020)
The growing recognition of how much principals matter for student learning and how they make a difference has fueled the need to ensure that effective principals are leading every school. One way to achieve this is through principal evaluation, which has experienced significant changes in the last decade. We conducted a national exploratory study (50 states) to document the trends in and provide an illustration of the current situation of states’ principal evaluation policies and practices. Using literature-based themes, our analysis of state statutes and regulations revealed that a majority of states have policies requiring at least one literature-based element. Only four (8%) states had statutes and/or regulations regarding allelements of principal evaluation that have been noted in the literature. Student achievement measures were the most common component—required in 66% of states. In addition, most states required principal evaluators to be trained and principals to be evaluated annually. We propose that future research focuses on the validity and reliability of measures and models used for principal evaluation—two aspects rarely addressed in principal evaluation policies—to ensure principal performance is meeting the needs of students, teachers, and schools.